Analisis Kritis Dialog Teologi Ibadah Dan Budaya Populer Dalam Konteks Kontemporer - Pusparani Sudaymin; Andries Yosua (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
The rapid growth of popular culture presents both challenges and opportunities for churches to conduct worship that remains relevant in the contemporary context. The gap between rigid traditional practices and modern life shaped by popular culture requires churches to find effective ways to communicate faith values. This study analyzes the relationship between worship theology and popular culture and explores how popular culture can strengthen faith without compromising spiritual depth. Using a qualitative, phenomenological-descriptive approach, the research examines the experiences, perceptions, and worship practices of congregations influenced by popular culture. Data were analyzed by identifying key themes and the relationships between worship theology elements—such as meaning, purpose, motivation, and liturgy—and the phenomenon of popular culture. The findings reveal that popular culture serves as a significant bridge between spirituality and modern life, fostering more contextual, interactive, and reflective expressions of faith. Elements such as contemporary music, digital media, and films function as effective means of theological communication and dialogue with daily life. However, churches must manage their use theologically to balance cultural relevance and spiritual depth. Thus, integrating popular culture into worship encourages the development of more inclusive, reflective, and meaningful worship experiences within the dynamics of modern society.